P207 The influence of obesity on the clinical outcome of benralizumab treatment in severe eosinophilic asthma a subgroup analysis from the BPAP study. (11th November 2022) - Nanzer, A; Burhan, H; Menzies-Gow, A; Rupani, H; Pfeffer, P; Clifton, I; Faruqi, S; Dhariwal, J; Morris, T; Lipworth, J; Watt, M; Jackson, DJ
Abstract : Introduction and Objectives: The BPAP study has previously described real-world outcomes of patients with severe eosinophilic asthma (SEA) following 1 year of treatment with benralizumab. It is recognised that obesity can be an independent driver of respiratory symptoms in patients with asthma and is associated with additional non-T2 inflammatory pathways. Whether co-morbid obesity in SEA is associated with a differential response to benralizumab treatment is poorly understood. Methods: The BPAP study is a retrospective, observational study of patients with SEA from eight UK centres. Clinical outcomes were described at baseline, 1 year and 2 years post-benralizumab initiation, and are presented for patients grouped by BMI (<30, ≥30–39 and ≥40, reported in this order throughout). Results: 258 patients with BMI recorded at baseline were included; 120 with BMI <30, 105 with BMI ≥30–39, and 33 with BMI ≥40. For these groups, the baseline annualised exacerbation rate (AER) was 4.6, 5.7, 6.1 (ANOVA, p=0.022); the baseline ACQ-6 was 2.7, 3.3, 3.8 (p<0.001); and the mean (SD) eosinophil count (cells/µL) was 744 (707), 574 (432) 462 (319), p=0.01. A relative reduction (vs baseline) in AER at 1 year was 78%, 81% and 70%, and at 2 years was 80%, 79% and 72%. The proportion who remained completely exacerbation-free at 2 years was 45%, 25% and 18% (p = 0.007). The proportion of OCS-dependent patients still requiring daily OCS for asthma at 2 years was 41%, 50%, 33% (p=0.53). The mean ACQ6 at 2 years was 1.3, 1.9, 1.7 whilst the proportion of patients achieving an ACQ-6 <1.5 at 2 years was 66%, 42%, 46% (p=0.03). Additional outcomes for patients who remained on treatment at 1 and 2 years are shown in table 1 . Conclusions: Patients with SEA and co-morbid obesity report a higher disease burden at baseline which may in part relate to the reduced likelihood of achieving a more complete cessation of asthma-related symptoms and exacerbations with benralizumab. However, further research is needed to understand whether additional obesity-related inflammatory pathways contribute to this residual disease burden in some patients. Please refer to page A216 for declarations of interest related to this abstract.